In vitro characterization of 4′-(p-toluenesulfonylamide)-4-hydroxychalcone using human liver microsomes and recombinant cytochrome P450s. (2nd April 2016) - Lee, Boram; Wu, Zhexue; Lee, Taeho; Tan, Xue Fei; Park, Ki Hun; Liu, Kwang-Hyeon
Abstract: 1. 4′-( p -Toluenesulfonylamide)-4-hydroxychalcone (TSAHC) is a synthetic sulfonylamino chalcone compound possessing anti-cancer properties. The aim of this study was to elucidate the metabolism of TSAHC in human liver microsomes (HLMs) and to characterize the cytochrome P450 (P450) enzymes that are involved in the metabolism of TSAHC. 2. TSAHC was incubated with HLMs or recombinant P450 isoforms (rP450) in the presence of an nicotinamide adenine dinucleotide phosphate, reduced form (NADPH)-regenerating system. The metabolites were identified and analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). P450 isoforms, responsible for TSAHC metabolite formation, were characterized by chemical inhibition and correlation studies in HLMs and enzyme kinetic studies with a panel of r P450 isoforms. 3. Two hydroxyl metabolites, that is M1 and M2, were produced from the human liver microsomal incubations ( K m and V max values were 2.46 µM and 85.1 pmol/min/mg protein for M1 and 9.98 µM and 32.1 pmol/min/mg protein for M2, respectively). The specific P450 isoforms responsible for two hydroxy-TSAHC formations were identified using a combination of chemical inhibition, correlation analysis and metabolism by expressed recombinant P450 isoforms. The known P450 enzyme activities and the rate of TSAHC metabolite formation in the 15 HLMs showed that TSAHC metabolism is correlated with CYP2C and CYP3A activity. The P450 isoform-selective inhibition study in HLMs and the incubation study of cDNA-expressed enzymes also showed that two hydroxyl metabolites M1 and M2 biotransformed from TSAHC are mainly mediated by CYP2C and CYP3A, respectively . These findings suggest that CYP2C8, CYP2C9, CYP2C19, CYP3A4 and CYP3A5 isoforms are major enzymes contributing to TSAHC metabolism.